2002
DOI: 10.1007/s15010-002-1083-8
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Pneumonia: A Cost-of-Illness Analysis

Abstract: The study gives insight into the structure of incremental cost caused by NP and shows that based on a conservative cost calculation the incremental cost per NP patient is higher for the hospital than for health insurance funds which indicates a significant financial deficit for the hospital. Antibiotics and microbiology together only contribute 6.8% to incremental cost. Therefore in a cost saving initiative their close relationship to length of hospitalization must be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 28 publications
1
25
0
7
Order By: Relevance
“…Trauma patients who develop ventilator-associated or community-acquired pneumonia have an increased hospital length of stay and more days of mechanical ventilation than do similarly injured patients who do not develop pneumonia [1][2][3]. A crucial aspect of the proper management of pneumonia is early detection and proper identification of the causative pathogen, which allows aggressive, targeted antibiotic therapy.…”
mentioning
confidence: 99%
“…Trauma patients who develop ventilator-associated or community-acquired pneumonia have an increased hospital length of stay and more days of mechanical ventilation than do similarly injured patients who do not develop pneumonia [1][2][3]. A crucial aspect of the proper management of pneumonia is early detection and proper identification of the causative pathogen, which allows aggressive, targeted antibiotic therapy.…”
mentioning
confidence: 99%
“…Given the cost of VAP [24,25], these programmes have shown themselves to be remarkably cost effective.…”
Section: Critical Care Healthcare Workersmentioning
confidence: 99%
“…A systematic audit of studies describing economic aspects of nosocomial infections revealed that costs for MRSA infections were highest with a mean of $35,367 [111]. A large fraction of additional costs that are attributed to the development of a nosocomial infection results from the prolonged hospital stay, rather than from the use of antibiotics to treat these infections [112]. The distribution of cost between hospital stay and costs of antibiotics might be different for infections caused by hVISA or VISA, especially if these infections are treated with relatively expensive antibiotics such as linezolid.…”
Section: The Cost Of Antibiotic Resistancementioning
confidence: 99%